The future of welfare services: How worried should we be about Wagner, Baumol and Ageing? - Andreas Bergh (Research Institute of Industrial Economics (IFN), 2016)
Welfare services are an important part of the Nordic welfare states both financially and for welfare state redistribution. Baumol's cost disease, Wagner's law, and population ageing are often said to bring challenges for the future provision of welfare services. While none of the three poses an immediate threat against the financial sustainability of the welfare state, they have important implications for distribution and for the political support for the welfare state. The combination demographic change, a higher relative price of welfare services and increasing demand for welfare services may force politicians to make a difficult choice between increasing taxes, allowing people to top up publicly financed services with additional private financing, or risk eroding support for the welfare state.
Keywords: H11; I38; J11; J18; 330; Welfare services; redistribution; Baumol's disease; Wagner's law; population aging